2020
DOI: 10.1002/ppp.2052
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in paleoclimatological studies of Arctic wedge‐ and pore‐ice stable‐water isotope records

Abstract: Late Pleistocene and Holocene ground ice are common throughout the Arctic. Some forms 12 of relict ground ice preserve local meteoric water, and their stable oxygen-and hydrogen-13 isotope ratios can be used to reconstruct past air temperatures. In this paper, we review the 14 formation and sampling of two forms of relict ground ice -wedge ice and pore ice -and 15 recent (2010-2019) advances in paleoclimatological studies of ground-ice stable-isotope 16 records in the Arctic. Recent advances are attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 64 publications
0
47
0
2
Order By: Relevance
“…Nevertheless, several studies (e.g. Mackay, 1983;Murton and French, 1994;Kotler and Burn, 2000;Schwamborn et al, 2006;Fritz et al, 2012) have shown that δ 18 O and δD isotopes in intra-sedimental ice can still reflect environmental and climatic changes when considered with caution and/or focused on pore ice Porter and Opel, 2020). Higher δ 18 O and δD but lower d values are found in MIS 3 compared to MIS 2 (Figs.…”
Section: Intra-sedimental Ice Characteristicsmentioning
confidence: 98%
“…Nevertheless, several studies (e.g. Mackay, 1983;Murton and French, 1994;Kotler and Burn, 2000;Schwamborn et al, 2006;Fritz et al, 2012) have shown that δ 18 O and δD isotopes in intra-sedimental ice can still reflect environmental and climatic changes when considered with caution and/or focused on pore ice Porter and Opel, 2020). Higher δ 18 O and δD but lower d values are found in MIS 3 compared to MIS 2 (Figs.…”
Section: Intra-sedimental Ice Characteristicsmentioning
confidence: 98%
“…Although the paleoclimate community is in the process of defining and adopting metadata conventions (Khider et al, 2019), the "bare minimum" current standards (e.g., ISO 19115 for geographic metadata) used by World Data System (WDS) repositories (e.g., NOAA Paleoclimatology, PANGAEA) are insufficient for characterizing water isotope proxy systems in a way that can be reliably applied to large-scale paleo-hydroclimate syntheses. One key example of this challenge is the temperature dependence of O-and Hisotopic fractionation, which has frequently been exploited to reconstruct past temperature changes in locations where air or water temperature exerts first-order influence on isotope ratios in precipitation and/or seawater (Kilbourne et al, 2008;Meyer et al, 2015;Porter et al, 2014). Yet in most places, the influence of temperature on isotopic fractionation is only one of many factors that influence the δ 18 O and δ 2 H of precipitation (Liu et al, 2012;Thomas et al, 2018) and seawater (Conroy et al, 2017;Partin et al, 2012;Russon et al, 2013).…”
Section: The Potential For a Network Of Paleo-water Isotope Records Tmentioning
confidence: 99%
“…1.2). For example, tree cellulose δ 18 O records have been interpreted to reflect temperature at midlatitude to high-latitude sites (e.g., Churakova (Sidorova) et al, 2019;Porter et al, 2014;Saurer et al, 2002;Sidorova et al, 2012) and precipitation amount in tropical or monsoonal sites (Brienen et al, 2013;Managave et al, 2011). As the δ 18 O of the soil water is also affected by evaporation of the soil water, precipitation minus evaporation (P − E) influences δ 18 O tree cellulose (Sano et al, 2012;Xu et al, 2018).…”
Section: Woodmentioning
confidence: 99%
“…1) The stable isotope compositions of the studied Sobo-Sise ice wedges do not show any significant differences between ice wedges of units A and B, corresponding to MIS 3 and 2, respectively. This might indicate that the globally cold LGM is not 530 reflected in the Sobo-Sise ice wedge-based winter climate record and would be in accordance with both regional scale, when compared to Bykovsky Peninsula (Meyer et al, 2002a) or to other study sites in the Laptev Sea region (Wetterich et al, 2011), and also Arctic-wide scale (Porter and Opel, 2020). It is not sufficiently resolved yet, whether this is due to a less cold…”
Section: Sob14-iw4mentioning
confidence: 90%
“…Nevertheless, several studies (e.g. Mackay, 1983;Murton and French, 1994;Kotler and Burn, 2000;Schwamborn et al, 2006;Fritz et al, 2012) have shown that δ 18 O and δD 475 isotopes in intrasedimental ice can still reflect environmental and climatic changes when considered with caution and/or focused on pore ice (Porter et al, 2019;Porter and Opel, 2020). Higher δ 18 O and δD, but lower d values are found in MIS 3 https://doi.org/10.5194/tc-2020-179 Preprint.…”
Section: Intrasedimental Ice Characteristicsmentioning
confidence: 99%